Assessment of Dry Eye in Post-Menopausal Women - Riaz, Irum; Awan, Muhammad Anwar; Munir, Zohra; Khan, Zaryab; Sabir Khan, Muhammad Aleem; Mehronisa (Medical Journal of South Punjab, 2024)
Objective: To find out the prevalence and severity of dry eye in Post-Menopausal Women.Methodology: This cross-sectional study included 59 participants who had been diagnosed with menopause based on their medical history. After acquiring signed consent, Patients were inquired about any ocular complaints of dry eye, and a Schirmer test was done using an anesthetic agent after they were comfortable. The ethics committee had already given their approval.Result: The current study included 59 post-menopausal women. The overall incidence of dry eye disease in postmenopausal women was found to be 43 (72.9%), which was statistically significant (p